Peningkatan Sikap Tentang Pemberian ASI melalui Couple Class - Ngestiningrum, Ayesha Hendriana; Nuryani, Nuryani (Jurnal Penelitian Kesehatan SUARA FORIKES, 2022)
Husband is a driving factor for breastfeeding. So far, education has often focused on pregnant women. One alternative solution to this problem is through the existence of a couple class. The purpose of this study was to analyze the effectiveness of the couples class in increasing attitudes about breastfeeding. The design of this research was pretest-posttest with control group. Respondents were 50 third trimester pregnant women and their partners, in two groups, each consisting of 25 people. The intervention group was given treatment in the form of a couple class. The control group received treatment according to the SOP in force at PMB. Attitudes were measured through filling out a questionnaire. Differences in attitude improvement between the two groups were analyzed using an independent sample t-test. The results of the analysis showed a value of p = 0.000, so it was interpreted that there were differences in attitude improvement between the intervention group and the control group. It was concluded that the couples class was effective in increasing attitudes about breastfeeding.Keywords: couple class; breast-feed; attitude; breast milk ABSTRAK Suami merupakan faktor pendorong pemberian air susu ibu. Selama ini edukasi sering berfokus pada ibu hamil. Salah satu alternatif pemecahan masalah ini adalah melalui keberadaan kelas pasangan. Tujuan dari penelitian ini adalah untuk menganalisis efektivitas kelas pasangan dalam meningkatkan sikap tentang pemberian air susu ibu. Desain penelitian ini adalah pretest-posttest with control group. Responden adalah 50 ibu hamil trimester III dan pasangannya, dalam dua kelompok, masing-masing terdiri atas 25 orang. Kelompok intervensi diberikan perlakuan berupa couple class. Kelompok kontrol mendapatkan perlakuan sesuai SOP yang berlaku di PMB. Sikap diukur melalui pengisian kuesioner. Perbedaan peningkatan sikap antara kedua kelompok dianalisis menggunakan independent sample t-test. Hasil analisis menunjukkan nilai p = 0,000, sehingga ditafsirkan bahwa terdapat perbedaan peningkatan sikap antara kelompok intervensi dan kelompok kontrol. Disimpulkan bahwa kelas pasangan efektif dalam meningkatkan sikap tentang pemberian air susu ibu.Kata kunci: couple class; menyusui; sikap; air susu ibu